IMPROVING THE SYSTEM OF EXERCISES THAT DEVELOP DIVERGENT THINKING OF ELEMENTARY SCHOOL STUDENTS (Academicia Globe: Inderscience Research, 2024)
This article discusses the use of methods for improving the system of exercises that develop divergent thinking in primary school students, types of methods, motivation for logical thinking.